Just take my heart [compact disc, unabridged] - Clark, Mary Higgins (Simon & Schuster Audio, 2009)
When her best childhood friend Natalie goes onto life support after an awful accident, Emily O'Connor, a 34-year-old professor at Boston Layman College, begs the hospital to use her dying friend's heart in a transplant. The transplant recipient? Emily's other best childhood friend, Alice. But with Natalie's death and Alice's heart surgery comes a series of unsettling and complex discoveries that may put Emily's own life in danger.